Layanan Prima dan Digitalisasi UMKM Sepatu, Sentra PIK Pulogadung - Laksamana, Patria; Saripudin, Saripudin; Suharyanto, Suharyanto; Sorongan, Fangky (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
The Covid-19 pandemic has had a significant impact on the retail sector, including the MSME leather shoes industry. One of them is the PIK Pulogadung area, which is known as a shopping center in Jakarta, which has experienced a decrease in customer visits resulting in a decrease in sales turnover. In addition, the lack of support from building managers in carrying out promotions and the Covid-19 pandemic are the biggest challenges for leather shoe stores in PIK Pulogadung. The solution to helping the leather shoe MSME industry is to provide excellent service and digitization. By prioritizing excellent service and adopting a digitization strategy, MSME leather shoe stores can improve operational efficiency, expand market reach, and provide customers with a superior shopping experience. Accessibility and Infrastructure Improvement, Education and Training Improvement, Technology Empowerment, Market Development and Promotion, Provision of Financial Support, Formation of Networks and Collaboration. With these steps, it is hoped that the small industrial village in Pulo Gadung can continue to grow and develop as an industrial center that is competitive, creates jobs, and makes a positive contribution to the regional economy